Potential Implications of China's 'One Belt, One Road' Strategies on Chinese International Migration - Raya Muttarak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
Along with the flows of China's foreign direct investment following the newly implemented 'One Belt, One Road' strategy by the Chinese government will likely generate movements of state employees, entrepreneurs, workers and accompanying family members to respective countries along the Belt and Road. It is not clear how large Chinese migration flows into these countries will be, who they are, how the public reception of the host society will be and how well the migrants will be integrated in the destination country. Based on extant data and literature on current Chinese migration, this paper describes trends and patterns of recent Chinese migration in Africa and Asia, analyses host country public perceptions on China and investigates integration patterns of Chinese migrants. Given that the 'One Belt, One Road' strategy has only been officially endorsed in 2015, it is still early to analyse its impacts on Chinese migration in the respective countries. Considering earlier Chinese overseas migration in the past decades, this paper presents potential migration and integration patterns one may expect following the Belt and Road initiative.
Keywords: 300; Attitude; China; integration; One Belt One Road; migrants; migration